Analysis of Sodium Chloride Intake and Treg/Th17 Lymphocytes in Healthy Individuals and Patients with Rheumatoid Arthritis or Systemic Lupus Erythematosus - Marlen Vitales-Noyola; Esther Layseca-Espinosa; Lourdes Baranda; Carlos Abud-Mendoza; Perla Niño-Moreno; Adriana Monsiváis-Urenda; Yvonne Rosenstein; Roberto González-Amaro (Journal of Immunology Research)
We assessed different immune parameters in patients with rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) with low (LSI) and high (HSI) sodium intake. Thirty-eight patients with RA, thirty-seven with SLE, and twenty-eight healthy subjects were studied and classified as LSI or HSI. Levels and suppressive function of CD4+CD25+Foxp3+ and CD4+CD69+Foxp3− Treg cells were determined by flow cytometry in blood samples. Levels and in vitro differentiation of Th17 cells were also assessed. Similar levels of CD4+CD25+Foxp3+ and CD4+CD69+Foxp3− Treg cells were observed in LSI and HSI patients or controls. However, a positive correlation was detected between sodium intake and levels of CD4+CD25+Foxp3+ Treg cells in SLE and a negative association between CD4+CD69+Foxp3− Treg cells and sodium intake in RA. No other significant associations were detected, including disease activity and sodium intake. Moreover, the suppressor activity of CD4+CD25+Foxp3+ and CD4+CD69+Foxp3− Treg cells was similar in LSI and HSI patients or controls. The levels and in vitro differentiation of Th17 cells were also similar in LSI and HSI individuals. Our results suggest that, in the population studied (Mexican mestizo), the level of sodium intake is not apparently associated with different relevant immune parameters in healthy subjects or patients with SLE or RA.